The Single-Nucleotide Polymorphism rs510432 in ATG5 Gene and the Development of Atopic March in Children - O.V. Iemets (Zaslavsky O.Yu., 2016)
Objective: to determine the association between single-nucleotide polymorphism rs510432 in gene ATG5 and the development of atopic march in children, to find out the probability of clinical manifestation and the features of the clinical course of atopic diseases in individuals with different allelic variants of polymorphism. Methods. Genotyping assay of polymorphism rs510432 in gene ATG5 was performed in children with atopic diseases and apparently healthy children using real-time polymerase chain reaction. Results. The minor T allele of rs510432 in ATG5 gene was significantly more often found in patients with atopic diseases than in apparently healthy children (χ2 = 6.36; р < 0.05). The results of logistic regression demonstrated that the risk of atopic diseases in children with minor genotype is 2.4 times higher than in carriers of major genotype. The average values of forced expiratory volume in 1 second (FEV1) are significantly lower in asthma patients with minor genotype than in thereof with major genotype (Q = 2.71; р < 0.05). There were no statistically significant differences in the distribution of allelic variants of rs510432 polymorphism of the gene ATG5 depending on the severity of bronchial asthma, atopic dermatitis and allergic rhinitis in children. Conclusions. Children with minor TT genotype of gene ATG5 polymorphism had an increased risk of atopic diseases, which is 72 %. In patients with bronchial asthma, minor TT genotype of gene ATG5 polymorphism has been associated with reduced FEV1. Rs510432 polymorphism of the gene ATG5 should be used to predict the development of atopic diseases in children.